Four Fragments on Drawing (diségno, 2017)
In 1954, I began sketching on a very regular basis, as if it were a task I had assigned myself, using the small Fabriano sketchpads with the blue covers. But I used to draw on any kind of paper, preferably on used paper (I used the back of drawing sheets found at school, old forms, and wrapping paper). I drew my own hand, sketches of classmates, landscapes, portraits. By 1958, I had learnt to draw very well but I am no longer able to make drawings like those I used to sketch on old grey wrapping paper. I began to paint, then I enrolled at the Architectural Faculty and at University, they taught me another type of drawing, precise and regular, which I had never been able to draw before. I learnt to keep my drawings and ideas in order, like books in a library. The drawings of other people began to be part of my own [...]